Five Year Plan 1978-83 Andhra Pradesh Draft Outline Vol. I - Planning Commission (Planning Commission, 1978)
While our approach to the plan of the State will have to be in consonance with the general approach of the Draft National Plan Document approved by the National Development Council, we have to necessarily take into account the circumstances obtaining in the State in formulating any meaningful strategy of development. Planning for development of Andhra Pradesh has to be visualised in terms of three different socio-economic regions.
Finance and Planning Department, Government of Andhra Pradesh